2015
DOI: 10.1007/s11888-015-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis for Colorectal Cancer Disparities

Abstract: African Americans suffer the highest burden from colorectal cancer (CRC) in the USA. Studies have suggested that healthcare access and poorer utilization of preventive services may be playing more of a role in this disparity. However, African Americans also tend to develop CRC at younger ages and are more likely to have proximal cancers. This raises the possibility of higher genetic predisposition to CRC among African Americans and this has not been well studied. In this article, we reviewed possible genetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…In other studies, risk factors including black race and a history of cancer or diabetes were closely related to RCC, while factors including white race, smoking, and high alcohol intake were closely associated with both LCC and ReC[1519]. Recent studies indicated that LCC had higher concentrations of human DNA in the stools than RCC[20], while RCC showed significantly higher mRNA expression levels of glycolysis genes than LCC[21].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, risk factors including black race and a history of cancer or diabetes were closely related to RCC, while factors including white race, smoking, and high alcohol intake were closely associated with both LCC and ReC[1519]. Recent studies indicated that LCC had higher concentrations of human DNA in the stools than RCC[20], while RCC showed significantly higher mRNA expression levels of glycolysis genes than LCC[21].…”
Section: Discussionmentioning
confidence: 99%
“…MSI-derived aberrations in chromosomes 11, 17p, and X are more prominent within the AA population when compared with Caucasians. Additionally, gene specific methylation changes in THRB, RAF1, LPL, DCC, XIST, PCNT, STS, TPD521.2, TOP1, and TNFRSF6B are all observably different between the two groups (11,81,82). These methylation discrepancies indicate that different sets of molecular markers are important in determining patients' susceptibility to various disease states.…”
Section: Insights From Other Cancersmentioning
confidence: 98%
“…По данным других популяционных исследований, локализация первичной опухоли в правых отделах также была ассоциирована с расой (негроидная) и наличием у больных сахарного диабета. Локализация опухоли слева была характерна для представителей европеоидной расы, курящих и злоупотребляющих алкоголем [34][35][36][37][38].…”
Section: популяционные данныеunclassified